Oral microbiome dysbiosis in women with a history of pregnancy loss: a metagenomic cross-sectional study - Ling Liu; Li Wei; Fang Xiang Mou; Wei Zhang; Rui Fang Wang; Qi Wang; Fang Wang (Scientific Reports)
Abstract Pregnancy loss is a prevalent condition among women of reproductive age, significantly affecting fertility and psychological well-being. Despite advances in understanding the etiology of pregnancy loss, the role of the oral microbiome—its composition and metabolic activity—in influencing pregnancy outcomes remains underexplored. Previous studies have suggested that imbalances in the microbiota may contribute to adverse health outcomes, but few have investigated its association with pregnancy loss specifically. A total of 182 women of childbearing age were recruited for this study and divided into two groups: those with a history of pregnancy loss (n = 70) and a control group with no history of adverse pregnancy outcomes (n = 112). Clinical data and buccal mucosa samples were collected for metagenomic analysis. The inclusion of participants was based on their reproductive history, with particular attention to selecting women with at least one confirmed pregnancy loss and those with at least one successful live birth to serve as controls. The oral microbiota of women in the pregnancy loss group exhibited significantly lower richness and diversity compared to the control group (p < 0.05). Notably, specific genera such as Faecalibacterium, Roseburia, and Bacteroides were positively correlated with pregnancy loss, whereas Pseudomonas and Leptotrichia were correlated with it. These findings suggest a potential microbial dysbiosis associated with pregnancy loss. Our study identifies significant oral microbiota dysbiosis in women with pregnancy loss, characterized by reduced diversity and altered metabolic pathways. These findings underscore the potential role of oral microbial imbalance in adverse pregnancy outcomes. While our cross-sectional design and sample heterogeneity limit causal inference, they highlight the need for longitudinal cohorts and mechanistic studies. Future research integrating multi-niche microbiome profiling (e.g., gut and vaginal microbiota) is essential to unravel systemic interactions and advance targeted interventions for reproductive health.